EFEKTIVITAS ORGANISASI SEKRETARIAT KPU DI DAERAH SEBAGAI THE OPERATING CORE DAN THE SUPPORT STAFF DALAM PENYELENGGARAAN PEMILU KEPALA DAERAH DAN WAKIL KEPALA DAERAH - Tatang Sudrajat (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2011)
From an organizational perspective, the existence of the Secretariat of the KPU in the regional (provincial, district / city) as the operating core as well as the support staff will determine the sting of the realization of a qualified election. This is relatedto organizational effectiveness with which the task will affect the quality of KPU and Regency / City KPU as the holder of the authority of the election of regional head and vice regional head (election). Important to know how the implementation oforganizational roles, the constraints facing the organization and affectiveness of the sekretariat as building an organization, so the achievement of objectives will determine the election as one of the important tasks of government.